Influence of Banjar Local Wisdom on Adolescents' Physical Activity to Mitigate Negative Effects of Gadget Use: A Health Promotion Model Approach - Heryyanoor Heryyanoor; Diana Hardiyanti; Siti Munawaroh; Siti Faridah; Ahmad Ramadhani (Indonesian Journal of Global Health Research, 2026)
Excessive use of gadgets, especially among adolescents, can reduce physical activity (AF) and increase sedentary behavior. This condition causes various physical and psychological health problems. Objective: This study aims to analyze the influence of Banjar local wisdom on adolescent AF in reducing the negative impacts of gadget use through the Health Promotion Model (HPM). A quasi-experimental design with a control group involving 60 adolescents in Banjar Regency, Indonesia. Proportional random sampling was used to determine that the intervention group (n=30) received education and direct practice of traditional Banjar games (Balogo, Egrang, Hadang). In contrast, the control group (n=30) received education through posters. AF, along with personal factors, knowledge, attitudes, and behaviors related to AF (HPM constructs), were measured before and after the intervention using a questionnaire and analyzed with the Wilcoxon Test and the Mann-Whitney Test. The results showed a significant increase in all variables in the intervention group (p = 0.001). The control group also showed a substantial increase in AF (p = 0.001) and knowledge (p = 0.001), but the increase was smaller than that of the intervention group. These findings suggest that integrating Banjar local wisdom into AF interventions can effectively promote a healthy lifestyle among adolescents. The HPM framework provides a valuable approach to understanding and facilitating behavior change. Further research is needed to explore this intervention's long-term effects and broader applicability.